2021
DOI: 10.18421/tem102-11
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Organizational Cynicism in the Relationship between Workplace Incivility and Organizational Silence

Abstract: In this study, the mediating role of "organizational cynicism" in the relationship between "rudeness in the workplace" and "organizational silence" was examined. The research is a quantitative research cross-sectional study. Research data were collected using a simple random sampling technique. Data analysis shows a significant and positive relationship between the participants' perceptions of rudeness in the workplace and organizational silence. It is understood that the perception of organizational cynicism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
(28 reference statements)
3
6
0
Order By: Relevance
“…K€ okalan, 2019). Earlier studies found that employee cynicism mediate the relationship between ostracism and deviant behavior (Otori et al, 2020), and between workplace incivility and organizational silence (Tutar et al, 2021). It is thus, assumed that cynicism has the capacity to mediate the relationship between perceived organizational politics and CWB.…”
Section: Employee Cynicism As a Mediatormentioning
confidence: 98%
“…K€ okalan, 2019). Earlier studies found that employee cynicism mediate the relationship between ostracism and deviant behavior (Otori et al, 2020), and between workplace incivility and organizational silence (Tutar et al, 2021). It is thus, assumed that cynicism has the capacity to mediate the relationship between perceived organizational politics and CWB.…”
Section: Employee Cynicism As a Mediatormentioning
confidence: 98%
“…The only study explaining the association amid workplace incivility and job search behaviour (Hassan et al , 2022) based on law enforcement organizations in the USA recommended investigating the said linkage in a post-pandemic scenario. Similarly, the outcome of workplace incivility in terms of the silent treatment displayed by the service sector employees is evident in only one study by Tutar et al (2021), which also does not discuss the outcomes in the light of moonlighting. Thus realizing such potential areas for inquiry, the study examines the effect of workplace incivility on job search behaviour and employee silence among Indian IT and information technology-enabled services (ITES) professionals.…”
Section: Introductionmentioning
confidence: 99%
“…The victims may start ignoring the instigator, deliberately lower their work efforts, be silent on organizational matters, gradually develop turnover intentions and exhibit job search behaviour. Several prior studies have examined the impact of workplace incivility on a range of damaging consequences, including turnover intention (Alola et al , 2021; Niven et al , 2021), organizational silence (Tutar et al , 2021), counterproductive work behaviour (Butt and Yazdani, 2021), deviant silence (Khan et al , 2021), psychological distress (Abubakar et al , 2018), knowledge hiding (Anand et al , 2022), job search behaviour (Hassan et al , 2022), emotional exhaustion (Moon and Morais, 2022) and many others.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations